The Qurʾānic Referential Dimension in Ibn al-Jawzī’s Akhbār al-Ẓuraf wa al-Mutmājīnīn (d. 597 AH) - ميري دعاء فاضل; جبار صلاح حسون (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The presence of religious authority in the books of literary heritage represents an effective value in the intellectual writings of their authors, due to its influential role in shaping the culture of the writer and the taste of the recipient. This is what we clearly observe in the use of Qur’anic verses in one of the books of literary heritage that adorned Arab libraries, and which is the purpose of our study, namely the book (Akhbar al-Zarraf wa al-Mutamajinn) by Abu al-Faraj Abd al-Rahman ibn Ali, Ibn al-Jawzi (d. 597 AH), who was known in his works for the breadth of his jurisprudence and preaching, as well as for the refined literary style in which he composed various books. The authentic religious source, especially the Qur’an, is considered one of the first and most important references in the author’s output and scientific writings. Without a doubt, it can be said that Ibn al-Jawzi found in the Holy Qur’an the best means to practice his scientific experiments in writing. Within the religious aspect, several levels fall, represented first by the Holy Qur’an in the highest level, which embodies the basic characteristic of religious discourse. Therefore, returning to it in the midst of literary production means giving distinctive credibility to the perceptions of the diverse literary discourse and its role in the taste of the recipient.